The Grapes of Math : Mind stretching math riddles - Tang, Greg.; Briggs, Harry (New York : Scholastic, 2001)
Illustrated riddles introduce strategies for solving a variety of math problems in using visual clues.
Keywords: Puzzles and games -- Juvenile literature